2013
DOI: 10.1590/0004-282x20130094
|View full text |Cite
|
Sign up to set email alerts
|

Patients with autosomal dominant spinocerebellar ataxia have more risk of falls, important balance impairment, and decreased ability to function

Abstract: Objectives: To assess balance and ability to function in patients with spinocerebellar ataxia. Methods: A total of 44 patients with different spinocerebellar ataxia types 1, 2, 3, and 6 were evaluated using the Tinetti balance and gait assessment and the functional independence measure. The scale for the assessment and rating of ataxia and the international cooperative ataxia rating scale were used to evaluate disease severity. Results: Most patients showed significant risk of falls. The balance scores were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Patients with other conditions that hampered their functional performance test results, such as Parkinson's disease, previous history of spine surgery, head trauma, current/old cerebrovascular events (cerebral hemorrhage and cerebral infarct), and other neurodegenerative conditions that could potentially affect functional mobility tests including Alzheimer's disease or a specific ataxic condition, were also excluded. [5][6][7][8] Furthermore, based on the whole length of lower extremities X-rays, patients with severe osteoarthropathic conditions that caused knee and hip joint contracture that affected whole spinal sagittal balance were also excluded from the patient pool. [9] Among the patients that met the inclusion criteria, six were lost to follow-up after 3 months or 1 year postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with other conditions that hampered their functional performance test results, such as Parkinson's disease, previous history of spine surgery, head trauma, current/old cerebrovascular events (cerebral hemorrhage and cerebral infarct), and other neurodegenerative conditions that could potentially affect functional mobility tests including Alzheimer's disease or a specific ataxic condition, were also excluded. [5][6][7][8] Furthermore, based on the whole length of lower extremities X-rays, patients with severe osteoarthropathic conditions that caused knee and hip joint contracture that affected whole spinal sagittal balance were also excluded from the patient pool. [9] Among the patients that met the inclusion criteria, six were lost to follow-up after 3 months or 1 year postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, repeated falls instill intense fear of falling, so that patients restrict their activities and become less independent, limiting their ability to perform physical activities, which in turn affects their posture and gait control 19 . In a study that assessed balance and functionality in 44 patients with SCA, Aizawa et al 20 concluded that individuals with SCA have significant balance impairment and an increased risk of falls and that this affects their ability to perform certain activities, such as self-care, transfers, locomotion and instrumental activities of daily living. They also concluded that the more severe the ataxia, the greater the balance and functional impairment, corroborating the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The management of mitochondrial diseases is usually supportive which includes: medications for diabetes mellitus, cardiac pacing, ptosis correction, intraocular lens replacement for cataracts, cochlear implantation for sensorineural hearing loss and symptomatic treatment for spasticity, chorea and epilepsy 43 . A great number of vitamins and co-factors have been used in individuals with mitochondrial disorders, although a recent Cochrane systematic review did not identify clear evidence supporting the use of any intervention in mitochondrial disorders 43 .…”
Section: Symptomatic Treatmentmentioning
confidence: 99%
“…A great number of vitamins and co-factors have been used in individuals with mitochondrial disorders, although a recent Cochrane systematic review did not identify clear evidence supporting the use of any intervention in mitochondrial disorders 43 . Some patients may have subjective benefit on treatment with CoQ10.…”
Section: Symptomatic Treatmentmentioning
confidence: 99%